Analisis Faktor-Faktor Produksi Domestik Yang Mempengaruhi Ekspor Kerajinan Kayu Di kecamatan Ubud Kabupaten Gianyar - Idayanti, Fitria; Dewi, Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
Wood craft Gianyar Regency is one of the leading commodities handicrafts penetrate export markets. Increased production value but not yet developed the factors of production. One of them the wood craft industry in the district of Ubud which has reached global markets. The purpose of this study to analyze the effect of direct and indirect,  labor capital and raw materials for export through the production of wood craft in gianyar ubud. This study uses primary data with a sample taken 89 units business. Data collected through observation, interviews and questionnaires. The analysis technique used is path analysis. Based on the analysis found that the Labor, Capital, Investment positive effect on production. Labor, Capital, Production, positive effect on exports. Raw materials has negative and significant effect on exports. Production is mediating variables in the indirect influence of Labor, Capital and Raw Materials on export.
Keywords: Labor, Capital, Raw Materials, Production, Export